2019
DOI: 10.3889/oamjms.2019.754
|View full text |Cite
|
Sign up to set email alerts
|

Case Series of Pre-Operative Endovascular Embolization of Nasopharyngeal Angiofibroma Using Polyvinyl Alcohol Foam Particle: A Single Centre Experience

Abstract: BACKGROUND:Nasopharyngeal Angiofibroma is a rare neoplasm in the sphenopalatine foramen. This tumour is histologically benign, but clinically malignant because it can erode the bone and surrounding structures, such as the pterygopalatine fossa, paranasal sinuses, and nasal cavity. It is a highly vascular tumour, sometimes from multiple Feeding arteries, and tends to bleed easily.CASE PRESENTATION:In these cases, series, we reported four cases of nasopharyngeal angiofibroma in children and one case in an elderl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Same result from other previous research Amran & Ashari, embolization of nasopharyngeal angiofibroma before resection is very useful to reduce perioperative complications of surgery. This procedure can reduce blood loss during tumor resection and provide better results [10]. Tumor staging and intraoperative bleeding are risk factors for residual juvenile nasopharyngeal angiofibroma [11].…”
Section: Discussionmentioning
confidence: 99%
“…Same result from other previous research Amran & Ashari, embolization of nasopharyngeal angiofibroma before resection is very useful to reduce perioperative complications of surgery. This procedure can reduce blood loss during tumor resection and provide better results [10]. Tumor staging and intraoperative bleeding are risk factors for residual juvenile nasopharyngeal angiofibroma [11].…”
Section: Discussionmentioning
confidence: 99%
“…In 2019, Amran and Bahar described the significance of preoperative embolization with polyvinyl alcohol in highly vascular tumors, such as nasopharyngeal angiofibroma. This procedure can reduce blood loss during the resection of the tumor [ 7 ]. Hence, preoperative embolization of the feeder's vessel was done with polyvinyl alcohol in our case.…”
Section: Discussionmentioning
confidence: 99%
“…Amran et al [17] demonstrated that the internal maxillary artery (IMA), a branch of the external carotid artery, is the main feeding artery for the JNA.…”
Section: Discussionmentioning
confidence: 99%